Downsizing and Heterogeneous Firing Costs - Pfann, Gerard A. (The Review of Economics and Statistics, 2006)
A structural labor demand model is developed that allows for worker heterogeneity regarding firing costs and productivity. It is estimated for a firm in demise when 3,650 workers were made redundant in a restructuring following bankruptcy. This was the largest mass layoff in the history of the Netherlands. The model produces sharp predictions on how firing thresholds depend on individual worker characteristics. The signs of the estimated coefficients are consistent with these predictions. The model correctly predicts 68% of individual worker displacement. The results provide new in-depth knowledge on how firing costs influence personnel decisions.